IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN BAHASA ARAB DI SEKOLAH PENGGERAK SMA MUHAMMADIYAH 1 JOMBANG - Nisa, Arienta Wardatun; Hikmah, Khizanatul (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The location of this research is at SMA Muhammadiyah 1 Jombang, this research aims to find out the implementation of the independent curriculum in Arabic language learning, supporting and inhibiting factors and solutions to inhibiting factors in the implementation of the independent curriculum in Arabic language learning at the driving school of SMA Muhammadiyah 1 Jombang. The method used in this research is descriptive qualitative method. The research data obtained will be analyzed in the form of interviews, observations and documentation. The results showed that the implementation of an independent curriculum in Arabic language learning at the driving school of SMA Muhammadiyah 1 Jombang was carried out in three stages, namely learning planning using teaching module guidelines, learning implementation including opening, core activities, closing and learning evaluation or assessment. In learning activities there are supporting factors and inhibiting factors. The supporting factors are divided into two factors, namely internal factors and external factors, including the quality of competent educators and interactive learning methods. The inhibiting factors are also divided into two, namely internal factors and external factors, including time management and lack of interest in learning Arabic, as well as solutions to internal factors and external factors of time management and lack of interest in learning Arabic.